The shorter multidrug-resistant tuberculosis treatment regimen in Singapore: are patients from South-East Asia eligible?. Issue 2 (10th August 2017) - Chee, Cynthia B.E.; KhinMar, Kyi-Win; Sng, Li-H.; Jureen, Roland; Cutter, Jeffery; Lee, Vernon J.M.; Wang, Yee-Tang
Multidrug-resistant tuberculosis (MDR-TB) is a major public health challenge, with an estimated 480 000 new cases emerging globally each year [1]. Treatment success rates using the 20-month conventional World Health Organization (WHO) regimen have been low, being about 52% in 2013 [1]. Observational studies in Bangladesh and several African countries have shown success rates of 84% using a shorter regimen [2–4]. Based on these studies, in May 2016 the WHO conditionally recommended a standardised, shorter 9–12-month regimen for MDR pulmonary tuberculosis (PTB), comprising a 4–6-month intensive phase with a combination of kanamycin, moxifloxacin, prothionamide, clofazimine, pyrazinamide, high-dose isoniazid and ethambutol, followed by a 5-month continuation phase containing moxifloxacin, clofazimine, ethambutol and pyrazinamide [5]. Confirmed resistance (except to isoniazid) or suspected ineffectiveness to a drug in this regimen is one of the exclusion criteria [5]. About 30% of MDR pulmonary-TB patients in a SE Asian (Singaporean) sample are eligible for the WHO shorter regimen http://ow.ly/KF3330dMSVs